Behavioural activation therapy for depression in adults with non‐communicable diseases - Uphoff, Eleonora (Cochrane Database Syst Rev, 2020)
BACKGROUND: Depression is common in people with non‐communicable diseases (NCDs) such as cardiovascular disease, diabetes, cancer, and chronic respiratory conditions. The co‐existence of depression and NCDs may affect health behaviours, compliance with treatment, physiological factors, and quality of life. This in turn is associated with worse outcomes for both conditions. Behavioural activation is not currently indicated for the treatment of depression in this population in the UK, but is increasingly being used to treat depression in adults. OBJECTIVES: To examine the effects of behavioural activation compared with any control group for the treatment of depression in adults with NCDs. To examine the effects of behavioural activation compared with each control group separately (no treatment, waiting list, other psychological therapy, pharmacological treatment, or any other type of treatment as usual) for the treatment of depression in adults with NCDs. SEARCH METHODS: We searched CCMD‐CTR, CENTRAL, Ovid MEDLINE, Embase, four other databases, and two trial registers on 4 October 2019 to identify randomised controlled trials (RCTs) of behavioural activation for depression in participants with NCDs, together with grey literature and reference checking. We applied no restrictions on date, language, or publication status to the searches. SELECTION CRITERIA: We included RCTs of behavioural activation for the treatment of depression in adults with one of four NCDs: cardiovascular disease, diabetes, cancer, and chronic respiratory conditions. Only participants with a formal diagnosis of both depression and an NCD were eligible. Studies were included if behavioural activation was the main component of the intervention. We included studies with any comparator that was not behavioural activation, and regardless of reported outcomes. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures expected by Cochrane, including independent screening of titles/abstracts and full‐text manuscripts, data extraction, and risk of bias assessments in duplicate. Where necessary, we contacted study authors for more information. MAIN RESULTS: We included two studies, contributing data from 181 participants to the analyses. Both studies recruited participants from US hospital clinics; one included people who were recovering from a stroke and the other women with breast cancer. For both studies, the intervention consisted of eight weeks of face‐to‐face behavioural therapy, with one study comparing to poststroke treatment as usual and the other comparing to problem‐solving therapy. Both studies were at risk of performance bias and potential conflict of interest arising from author involvement in the development of the intervention. For one study, risks of selection bias and reporting bias were unclear and the study was judged at high risk of attrition bias. Treatment efficacy (remission) was greater for behavioural activation than for comparators in the short term (risk ratio (RR) 1.53, 95% confidence interval (CI) 0.98 to 2.38; low‐certainty evidence) and medium term (RR 1.76, 95% CI 1.01 to 3.08; moderate‐certainty evidence), but these estimates lacked precision and effects were reduced in the long term (RR 1.42, 95% CI 0.91 to 2.23; moderate‐certainty evidence). We found no evidence of a difference in treatment acceptability in the short term (RR 1.81, 95% CI 0.68 to 4.82) and medium term (RR 0.88, 95% CI 0.25 to 3.10) (low‐certainty evidence). There was no evidence of a difference in depression symptoms between behavioural activation and comparators (short term: MD –1.15, 95% CI –2.71 to 0.41; low‐certainty evidence). One study found no difference for quality of life (short term: MD 0.40, 95% CI –0.16 to 0.96; low‐certainty evidence), functioning (short term: MD 2.70, 95% CI –6.99 to 12.39; low‐certainty evidence), and anxiety symptoms (short term: MD –1.70, 95% CI –4.50 to 1.10; low‐certainty evidence). Neither study reported data on adverse effects. AUTHORS' CONCLUSIONS: Evidence from this review was not sufficient to draw conclusions on the efficacy and acceptability of behavioural activation for the treatment of depression in adults with NCDs. A future review may wish to include, or focus on, studies of people with subthreshold depression or depression symptoms without a formal diagnosis, as this may inform whether behavioural activation could be used to treat mild or undiagnosed (or both) depressive symptoms in people with NCDs. Evidence from low‐resource settings including low‐ and middle‐income countries, for which behavioural activation may offer a feasible alternative to other treatments for depression, would be of interest.